EXCISE TAXES (Tufts Archival Research Center, 2007)
Report by the Tobacco Institute regarding a proposal by the House Ways and Means Committee to raise excise taxes. Presents arguments from several organizations, including the Citizens for Tax Justice (CTJ), and the Economics Policy Institute (EPI), that disagree with this means to raise money for health care. Argues that the tax will fall most heavily on the average tax payer. Includes updates on several activities the Tobacco Institute is involved in to prevent the raise in the tax.